Iterative demodulation and decoding of practical DS-CDMA signals - Li, Ge. (2008)
Iterative decoding techniques have become a viable alternative for construct-ing high performance coding systems. In particular, the recent success of Turbo codes indicates that performance close to the Shannon limit may be achieved with reasonable complexity. In this thesis, we extend the iterative decoding pro-cess to the uplink transmission of a direct sequence(DS) code division multiple access (CDMA) system using M-ary orthogonal Walsh Hadamard (WH) signal-ing and noncoherent detection. In such a communication system, the successive implementation of orthogonal signal modulation-set mapping and conventional forward error correction can be viewed as a form of serially concatenated coding. Thus the demodulation and decoding functions of the DS-CDMA signals can be combined in one single iterative decoder module.